Weakly P-small not P-small subsets in Abelian groups - Banakh, T.; Lyaskovska, N. (Algebra and Discrete Mathematics, 2006)
Answering a question of D. Dikranjan and I. Protasov we prove that each infinite Abelian group contains a weakly P-small subset that is not P-small.